Improving Early Childhood Learning Concentration through Brain Games and Brain Gymnastics: Peningkatan Konsentrasi Belajar Anak Usia Dini melalui Brain Games dan Senam Otak - Rusnaini (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
Attention span is a crucial executive function that significantly influences early childhood learning outcomes. However, excessive screen time exposure and sedentary lifestyles have led to declining attention spans among young children. This study aims to improve the learning concentration of early childhood through brain games and brain gym activities at TK Mukti Tama III B. This research employs Classroom Action Research (PTK) using the Kemmis and McTaggart model, conducted in two cycles. The subjects were 20 children (10 boys and 10 girls) aged 5-6 years in Group B. Data collection techniques included observation, documentation, field notes, and unstructured interviews, analyzed using descriptive qualitative and quantitative methods. The results showed a significant improvement in children's learning concentration. In the pre-cycle, only 30% of children reached the expected developmental milestones (BSH/BSB). This increased to 60% in Cycle I and reached 85% in Cycle II. The integration of brain games (puzzle, memory games, pattern recognition) and brain gym activities (cross crawl, hook-ups, lazy holds) based on Dennison's Brain Gym theory successfully enhanced children's sustained attention, selective attention, and cognitive flexibility. The study concludes that brain games and brain gym activities are effective pedagogical interventions for improving early childhood learning concentration.